Cast apart by the elites: how status influences assortative matching in industrial clusters. Issue 7 (9th August 2021) - Maghssudipour, Amir; Balland, Pierre Alexandre; Giuliani, Elisa
ABSTRACT: In this article we investigate how status considerations influence inter-firm knowledge transfer in industrial clusters. Using evidence of a highly dynamic wine cluster and network analysis methods of Stochastic Actor-Oriented Modelling, we find that status considerations drive assortative matching in the formation of ties within a cluster. This means that low-status firms are cast from the 'circles that count', while high-status firms are likely to interact with similar others. Far from being an equal space of knowledge sharing, some clusters may instead be spaces of social hierarchies and elitist ties.